2006
DOI: 10.1038/sj.cdd.4402011
|View full text |Cite
|
Sign up to set email alerts
|

Src-family tyrosine kinase fyn phosphorylates phosphatidylinositol 3-kinase enhancer-activating Akt, preventing its apoptotic cleavage and promoting cell survival

Abstract: Phosphatidylinositol 3-kinase enhancer-activating Akt (PIKE-A) binds Akt and upregulates its kinase activity, preventing apoptosis. PIKE-A can be potently phosphorylated on tyrosine residues 682 and 774, leading to its resistance to caspase cleavage. However, the upstream tyrosine kinases responsible for PIKE-A phosphorylation and subsequent physiological significance remain unknown. Here, we show that PIKE-A can be cleaved by the active apoptosome at both D474 and D592 residues. Employing fyn-deficient mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Noticeably, compared to FynD cells, PIKE-L apoptotic cleavage is partially decreased in FynA cells (Supplemental Figure 1C, right lower panel), an effect similar to netrin-1-treated cells. PIKE-A is mainly phosphorylated by Fyn on Y681 and Y774 residues 14 , which correspond to Y1032 and Y1124 in PIKE-L. Immunoprecipitation assay reveals that wild-type PIKE-L strongly interacts with UNC5B, whereas Y1032F, Y1124F and Y1032, 1124F mutants fail to interact with UNC5B. As expected, PIKE-L wild-type is evidently tyrosine phosphorylated, which is abolished in PIKE-L mutants ( Figure 3A, top and 2 nd panels).…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Noticeably, compared to FynD cells, PIKE-L apoptotic cleavage is partially decreased in FynA cells (Supplemental Figure 1C, right lower panel), an effect similar to netrin-1-treated cells. PIKE-A is mainly phosphorylated by Fyn on Y681 and Y774 residues 14 , which correspond to Y1032 and Y1124 in PIKE-L. Immunoprecipitation assay reveals that wild-type PIKE-L strongly interacts with UNC5B, whereas Y1032F, Y1124F and Y1032, 1124F mutants fail to interact with UNC5B. As expected, PIKE-L wild-type is evidently tyrosine phosphorylated, which is abolished in PIKE-L mutants ( Figure 3A, top and 2 nd panels).…”
supporting
confidence: 67%
“…PIKE can be phosphorylated on tyrosine residues by Fyn 14 . Netrin-1 has also been shown to trigger its receptor DCC tyrosine phosphorylation 15 -18 .…”
mentioning
confidence: 99%
“…Fyn is intimately correlated with the phosphoinositide-3-kinase/Akt signaling pathway (Lue et al, 2007;Tang et al, 2007;Holen et al, 2008) and prompts proliferation and differentiation (Kim et al, 2010). Akt plays an important role in cell survival and the development of cancer (Brauer and Tyner, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…28 Further, PIKE-A interacts with insulin receptor and mediates its suppressive effect on AMPK activation. 29 Previously, we have reported that Fyn phosphorylates PIKE-A on both Y682 and Y774 30 and regulates its interaction with different partners, promoting neuronal survival 31 and adiposeness. 32 In this report, we provide new evidence supporting that Fyn phosphorylation of PIKE-A is critical for its association with AMPK and inhibition of its kinase activity, leading to the blockade of cell proliferation.…”
mentioning
confidence: 99%